Assessing People's Awareness of Environmental and Health Impacts of Straw Burning in Southeast Vietnam Through Factor Analysis and Proposing Sustainable Solutions - Van-Phuc Dinh; Bich-Ngoc Duong; Thi-; Thanh Tran; Duy-Khoi Nguyen; Thi Cam Quyen Ngo; Bich Ngoc Hoang; Thanh Q. Nguyen (SAGE Publishing, 2024)
Rice production in Southeast Vietnam generates a large amount of straw, which is often burnt directly in fields, causing air pollution and affecting community health. This study aims to assess the awareness of the environmental and health impacts of straw burning among farmers, students, and managers in the provinces of Tay Ninh, Binh Phuoc, and Dong Nai, Vietnam. We conducted a survey of 686 individuals, divided into 3 main groups: 349 farmers, 250 students, and 87 local government officials. The survey results, analyzed using exploratory factor analysis (EFA), indicate that 55.2% of farmers never engage in straw burning, while 24.4% report infrequent burning. Awareness of the negative impacts, such as ecological imbalance, air pollution, and soil degradation, is prevalent, particularly among students and managers. Statistical analysis revealed significant differences in perception and behavior toward straw burning among the groups. Despite the willingness of farmers to adopt sustainable straw management practices, they require low-cost solutions that do not significantly alter their farming practices. This study proposes a policy framework that includes educational initiatives, community participation, and government support to promote sustainable straw management. By guiding farmers away from straw burning, the framework aims to reduce air pollution and contribute to environmental protection and sustainable agricultural development.